Should we train as we compete? Games might be the best scenario to reach the internal peak demands in professional basketball players - Pérez-Chao, E. A.; Ribas, C.; Gómez, M. A.; Portes, R.; Jiménez, S. L.; Lorenzo, A. (Medicina dello Sport, 2022)
BACKGROUND The aim of this study was to compare the internal peak demands (PD) of different training sessions and official matches in professional basketball players.